Relationship between Very Low Birth Weight Neonates and increased Neonatal mortality for age 0 to 7 days - Hussein, Hafadh Jaleel; Kadhum, Nidhal M.; Muneeb, Aeshah; Salih, Luay M. (AL-Kindy College Medical Journal, 2014)
B aa cc kk gg r oo uu nn dd : Very low birth weight (VLBW) neonates constitute approximately 4–7 percent of all live births and their mortality is very high. O bb j ee cc t i vv ee: to find out if there is a relationship between Very Low Birth Weight Neonates and increased neonatal mortality for age 0 to 7 days. M ee t hh oo dd ss A retrospective study of VLBW neonates admitted to NICU at Ibn Al- Baladi Pediatrics and Maternity hospital over one year (2012)were studied, study period was from April till August 2013. Exclusion criteria were: (1) neonates weighing less than 700 g and with gestational age less than 24 weeks (abortion) (2) death in the delivery room (3) neonates weighing more than 1500 g. (4) Postnatal age more than 7 days. The outcome measure was in-hospital death. Medical records were reviewed and data were analyzed. Results being considered as statistically significant when the P value was≤0.05. R ee ss uu l t A total of 150 cases of very low birth weight (VLBW) neonates were enrolled, of which a total of 69 (46 %) babies died. The survival rate was found to increase with the increase in birth weight and gestational age (P value was highly significant). There is no relation between gender, postnatal age, mode of delivery and social class with number of death. Respiratory distress, gestational age, neonatal septicaemia are the factors directly responsible for neonatal mortality. Premature rupture of membranes (PROM), multiple pregnancy and Young mothers were the most common maternal risk factors associated with death in VLBW. C oo nn cc l uu ss i oo nn ss : Mortality rate in VLBW neonates was found to increase with the decrease in birth weight and gestational age. prematurity, RDS and infection are major causes of perinatal deaths. Advanced medical care must be available in each neonatal care unit including, Artificial ventilation, pulse oximetry and Surfactant.Obstetricians must be advised for Intense and regular follow up of at risk mothers( multiple pregnancy, PROM, IUGR, APH).